Oxidative Bioconversion of Cholesterol by Pseudomonas sp. Strain ST-200 in a Water-Organic Solvent Two-Phase System - Aono, Rikizo (1994)
Pseudomonas sp. strain ST-200, which is capable of conversion of cholesterol, was isolated from humus soil. This organism effectively modified cholesterol dissolved in an organic solvent by dehydrogenation and oxygenation. When the organism was grown in a medium overlaid with a 10% volume of a mixed organic solvent (p-xylene and diphenylmethane; 3:7, vol/vol) containing cholesterol (20 mg/ml), the cholesterol concentration in the organic solvent was reduced to only 0.4 mg/ml after 8 days. Although the organism did not assimilate cholesterol, 98% of the cholesterol initially present disappeared. The organic solvent layer contained two major and three minor compounds converted from cholesterol. The major compounds were 6β-hydroxycholest-4-en-3-one (8.9 mg/ml) and cholest-4-ene-3,6-dione (7.6 mg/ml). The concentrations of these compounds were equivalent to 43 and 37% of the cholesterol initially present. This organism would provide an effective and convenient system to oxidize the C-3 and -6 positions of cholesterol by introduction of a hydroxyl or ketone group.